EPULIS FISSURATUM CAUSED BY CHRONIC IRRITATION FROM THE USE OF COMPLETE DENTURES: A CASE REPORT - Nurhayati, Sri; Chuan, How Kim; Angela, Emerentia; Halim, Susanna (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
Epulis fissuratum is a reactive fibrous hyperplasia commonly caused by chronic mechanical irritation from ill-fitting complete dentures. It often presents as mucosal folds in the vestibular area of the oral cavity. Aim: This case report aims to describe the clinical features, etiological factors, management strategies, and the role of patient education in preventing recurrence. A 65-year-old female patient presented with a soft tissue enlargement in the mandibular vestibule, associated with prolonged use of unadjusted complete dentures. Clinical examination and patient history confirmed the diagnosis of epulis fissuratum. Conservative surgical excision was performed under local anesthesia, followed by prosthetic rehabilitation and oral hygiene education. Postoperative healing was uneventful, with complete tissue recovery observed within two weeks. A new denture was fabricated to accommodate the anatomical changes and prevent further trauma. Monthly follow-ups for three months showed no signs of recurrence, and the patient reported improved comfort and satisfaction. Chronic irritation from ill-fitting dentures remains a major contributor to soft tissue lesions such as epulis fissuratum. Early detection, surgical intervention when needed, and appropriate prosthetic management—combined with effective patient education—are key to successful outcomes. Denture users should be advised of the importance of routine evaluations to ensure long-term oral health and prevent recurrence of such lesions. ABSTRAKEpulis fissuratum adalah hiperplasia fibrosa reaktif yang umumnya disebabkan oleh iritasi mekanis kronis akibat gigi tiruan lengkap yang tidak pas. Kondisi ini sering muncul sebagai lipatan mukosa di area vestibulum rongga mulut. Tujuan: Laporan kasus ini bertujuan untuk menjelaskan gambaran klinis, faktor etiologi, strategi penatalaksanaan, dan peran edukasi pasien dalam mencegah kekambuhan. Seorang pasien perempuan berusia 65 tahun datang dengan keluhan pembesaran jaringan lunak di vestibulum mandibula, yang berhubungan dengan penggunaan gigi tiruan lengkap yang tidak disesuaikan dalam jangka waktu lama. Pemeriksaan klinis dan riwayat pasien memastikan diagnosis epulis fissuratum. Eksisi bedah konservatif dilakukan dengan anestesi lokal, diikuti dengan rehabilitasi prostetik dan edukasi kebersihan mulut. Penyembuhan pascaoperasi berjalan lancar, dengan pemulihan jaringan lengkap yang diamati dalam dua minggu. Gigi tiruan baru dibuat untuk mengakomodasi perubahan anatomi dan mencegah trauma lebih lanjut. Tindak lanjut bulanan selama tiga bulan tidak menunjukkan tanda-tanda kekambuhan, dan pasien melaporkan peningkatan kenyamanan dan kepuasan. Iritasi kronis akibat gigi palsu yang tidak pas tetap menjadi penyebab utama lesi jaringan lunak seperti epulis fissuratum. Deteksi dini, intervensi bedah bila diperlukan, dan manajemen prostetik yang tepat—dikombinasikan dengan edukasi pasien yang efektif—merupakan kunci keberhasilan. Pengguna gigi palsu harus diberi tahu tentang pentingnya evaluasi rutin untuk memastikan kesehatan mulut jangka panjang dan mencegah kekambuhan lesi tersebut.